2002
DOI: 10.1073/pnas.122614399
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of organic matter in a highly disturbed estuary: The role of detrital and algal resources

Abstract: The importance of algal and detrital food supplies to the planktonic food web of a highly disturbed, estuarine ecosystem was evaluated in response to declining zooplankton and fish populations. We assessed organic matter bioavailability among a diversity of habitats and hydrologic inputs over 2 years in San Francisco Estuary's Sacramento-San Joaquin River Delta. Results show that bioavailable dissolved organic carbon from external riverine sources supports a large component of ecosystem metabolism. However, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 37 publications
2
100
0
Order By: Relevance
“…Our study provides further evidence to show that, while terrestrially derived organic material commonly enters estuaries in relatively large amounts when associated with sedimentation events, it does not necessarily represent a nutritionally important or utilisable food source (e.g. Sobczak et al 2002).…”
Section: Sediment Characteristics Correlated With Macrofaunamentioning
confidence: 63%
“…Our study provides further evidence to show that, while terrestrially derived organic material commonly enters estuaries in relatively large amounts when associated with sedimentation events, it does not necessarily represent a nutritionally important or utilisable food source (e.g. Sobczak et al 2002).…”
Section: Sediment Characteristics Correlated With Macrofaunamentioning
confidence: 63%
“…Given the allochthonous nature of combined dissolved and particulate organic matter in these lakes, it is striking that terrestrial organic matter comprises only 25-30% of zooplankton biomass. The relatively high reliance on algal material demonstrates that zooplankton are quite selective in keeping with physiological studies (51,52) and some field studies (22,23).…”
Section: Tdpl Tpl Tdp Tp Td Tpchmentioning
confidence: 67%
“…A variety of organic carbon sources may support coastal and estuarine consumers, including phytoplankton (Canuel et al 1995;Deegan and Garritt 1997;Sobczak et al 2002;Howe and Simenstad 2007), submerged aquatic vegetation (SAV;Fry 1981;Kitting et al 1984), benthic algae (Hecky and Hesslein 1995;Deegan and Garritt 1997;Kwak and Zedler 1997;Page 1997), epiphytic macroalgae (Kitting et al 1984;Moncrieff and Sullivan 2001;Vizzini et al 2002), and terrestrial vegetation (Chanton and Lewis 2002).…”
mentioning
confidence: 99%
“…These studies have demonstrated the importance of in situ phytoplankton production as the primary source of available organic carbon for pelagic consumers in the tidal freshwater region of the estuary (Canuel et al 1995;Jassby and Cloern 2000;Mueller-Solger et al 2002;Sobczak et al 2002Sobczak et al , 2005. However, the relative importance of phytoplankton as an energy source for consumers in other habitats is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation